ON THE EVOLUTION OF IRANIAN POLICIES IN THE SOUTHERN CAUCASUS - VARTANIAN, Arsen (CENTRAL ASIA AND THE CAUCASUS, 2004)
It is a well-known fact that the events of 9/11 and the subsequent antiterrorist operation in Afghani-stan, as well as the situation in Iraq have influenced Iranian foreign policy strategies. They produced, in particular, a gradual transformation of the foreign policy concepts Tehran was applying in the region. The ambitious concept of the regional leadership, which has been developed since the time of the Shahs, has undergone a profound change. At present, when the U.S. is successfully establishing their presence in Afghanistan and Iraq, and penetrating into the Southern Caucasus and Central Asia, Iranian leadership does not declare any longer that it aims for military superiority over the neighboring countries.instead, Tehran is adopting a stance of “positive neutrality” with its neighbors.1 On the other hand,Mr. A. Shamkhani, the Iranian Defense Minister, keeps emphasizing that Iranian military capacity is “sufficient to rebuff any military aggression.”2 At the same time, Iranian leaders pay utmost attention to the increase of their political role and influence in the region. In particular, they are keen to take part in the reconstruction of Iraq and Afghanistan, while at the same time boosting up their own economy for the sake of a stronger role in the Middle East. Another dimension of Tehran’s new foreign policy is presenting itself as “an Islamic democracy,” a synthesis of Islamic and democratic traditions, and distancing it-self from terrorist organizations, such as al-Qa’eda and the Taliban. The Southern Caucasus has always been in the sphere of Iran’s foreign policy interests, taking into account their historical links and geographic proximity. Since the collapse of the U.S.S.R. Tehran has been trying to establish equal relations based on trust with the three South Caucasian countries, despite the disagreements among them. Iranian analysts believe that this constructive approach brought positive results in the early 1990s. In this way Iran’s policy was different from that of Turkey’s, which adopted an anti-Armenian stance on the Karabakh issue. As a result, it cannot establish normal relationships with Erevan to this day, which limits Ankara’s opportunities in the region.